2013
DOI: 10.1108/14626001311326752
|View full text |Cite
|
Sign up to set email alerts
|

Financial availability and government support for women entrepreneurs in transitional economies

Abstract: Purpose -This paper studies female entrepreneurship in two post-Soviet countries -Russia and Ukraine. Employing institutional theory, the research aims to investigate the entrepreneurial environment, particularly government support programmes and the availability of financial resources, with a focus on women entrepreneurs. Design/methodology/approach -This research is a qualitative investigation that comprises 60 interviews with Russian and Ukrainian entrepreneurs, bank officers and representatives of governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 51 publications
2
71
1
2
Order By: Relevance
“…Also according to Iakovleva, Solesvik and Trifilova (2013) there are no gender differences in bank financing found in Russia and Ukraine. Authors found that being a woman is not a disadvantage to get bank loans; both men and women are getting the same priority for bank finance.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 1 more Smart Citation
“…Also according to Iakovleva, Solesvik and Trifilova (2013) there are no gender differences in bank financing found in Russia and Ukraine. Authors found that being a woman is not a disadvantage to get bank loans; both men and women are getting the same priority for bank finance.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…The findings of the research of Iakovleva, Solesvik and Trifilova (2013) find that in Russia and Ukraine most of the women entrepreneurs in both countries are not even aware of any kind of financial support from the government to start an enterprise. There are some entrepreneurs who were aware of the government support but they did not apply due to too much legislative regulations of the funds.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Brush et al (2009) argued that motherhood or family/household contexts might have a larger impact on women than men, while Welter and Smallbone (2010) illustrated that this context might be very different depending on the country of operation. For example, in a recent study of entrepreneurial intentions in two developed and two developing countries, it was found that the highest barrier for starting a business is indeed risk related (Iakovleva et al 2013). However, that was not the case for developing countries, where risk barrier was ranked second or third.…”
Section: Using Family and Gender As Explanatory Variablesmentioning
confidence: 99%
“…Nearly 10 years later a new wave targeting small business began, and today banks offer a wide range of services, including loans, for the SME sector. However, the interest rate for loans is quite high, and many start-ups chose to use other, informal, sources of funding (Iakovleva et al 2013). Although few in number, there are programs to support entrepreneurs with venture capital, mortgages, or business incubation.…”
Section: Entrepreneurship In the Russian Contextmentioning
confidence: 99%
“…Additional share issuance can be a source of significant amount of resources for enterprise development [Iakovleva et al 2013, Solesvik 2012, Sonenshein 2014. Equity issuance and corporate dividend policy should meet the interests of shareholders, including minority ones, and create conditions for sustainable corporate development.…”
Section: Introductionmentioning
confidence: 99%